PENINGKATAN KETERAMPILAN BERBICARA MELALUI METODE BERMAIN TEKA-TEKI SISWA KELAS X MAS-TI TABEK GADANG KABUPATEN LIMA PULUH KOTA - Ayu Gustia Ningsih; Atmazaki .; Syahrul R (Bahasa, Sastra, dan Pembelajaran, 2013)
Abstract: One of basic components in teaching learning process is speaking skill. The aim of this research was to describe the process, result, and factors that influence the improvement of speaking skill by using Riddle game. The research was classified into classroom action research. The sample was students at tenth grade MAS-TI Tabek Gadang, Lima Puluh Kota Regency. The data were collected by using observation, questionnaire, field note, and test. The data were quantitatively and qualitatively analyzed.  The findings of the research revealed that the riddle game could improve the students’ speaking skill. The students were asking and answering questions actively, moreover they could expressed the idea and give some explanation precisely. It was valuable in the sense that it helped the students to improve their speaking skill. Kata kunci: keterampilan berbicara, metode bermain teka-teki